PEMANFAATAN LINGKUNGAN SEBAGAI PEMBELAJARAN PENJAS SDN KLAMPIS BARAT BANGKALAN - Fajar Hamdhan Utama; Septyaningrum Putri Purwoto; Heni Yuli Handayani; Haryo Mukti Widodo (SATRIA : Journal of Sports Athleticism in Teaching and Recreation on Interdisciplinary Analysis, 2022)
This research is a literature study that looks at learning resources, especially the environment as a learning medium for students in elementary schools. The environment is a learning object that can be seen by students and can be shown directly to students. We hope that utilizing the environment as a learning resource will help improve the quality of student learning in the learning process. As a result, the researcher collected and analyzed secondary data, showing that learning through the use of the environment provided a positive stimulus for students to easily understand the material. Utilization of the coastal environment as a learning medium by considering the many benefits of doing sports in the coastal environment such as the risk of injury on the sand tends to be lower than when running on a hard surface and the relatively clean air on the beach can make students comfortable to exercise so that The use of this physical education learning environment is very appropriate. In addition, the teacher uses the beach environment as a medium for recreation or vacation in order to relieve fatigue from studying in the classroom.